The Influence of Government Supervision and SAKIP to Implementation Good Governance in Ditjen Binwasnaker & K3 Kementrian Ketenagakerjaan Republik Indonesia - Kuncoro, Bagus; Purba, Rahima; Maisyarah, Renny (IJBLE Scientific Publications Community Inc., 2024)
The purpose of this study is to determine whether government supervision and implementation of SAKIP have an effect on Good Governance. The design of this research is quantitative, namely research to identify and show the influence of a variable on other variables. The research population includes employees in Ditjen Binwasnaker & K3 Kementrian Ketenagakerjaan Republik Indonesia is totaling 472 respondents. Slovin-based sampling technique will be used to identify the total population to be taken according to its proportion in each section until the end of the targeted 217 employee samples. This study uses data analysis techniques Structural Equation Modelling - PLS (SEM-PLS). The results of the hypothesis testing prove that Government Supervision has an effect on Good Governance. Specifically, the research findings conclude that Government Supervision can improve Good Governance. The implementation of SAKIP has an effect on Good Governance. Specifically, the research findings conclude that the implementation of SAKIP can improve Good Governance.